FLEKSIBILITAS NILAI TUKAR DAN PENYESUAIAN TRANSAKSI BERJALAN DI INDONESIA: ANALISIS THRESHOLD VAR - Farhana Zahrotunnisa; Iman Sugema; Toni Bakhtiar (JURNAL EKONOMI DAN KEBIJAKAN PEMBANGUNAN, 2015)
Estimation study about the relationship between exchange rate flexibility and current account adjustment has been through three stages, the first stage was analysis of correlation among exchange rates variability (proxied by REER and NEER) and exchange rate regimes classification. The second step was estimating the relationship that the former was mentioned with VAR as benchmark model. The third step was applying the nonlinear estimation with Threshold VAR. The results of analysis showed that exchange rate regime classification may not capture actual exchange rate variability and flexibility exchange rate can accelerate current account adjustment in Indonesia if the changes of Indonesia exchange rate less than 27.7059 (low regime) whereas in high regime exchange rate is persistent increasing so that the system between exchange rate and current account become unstable. Bank Indonesia as monetary authorities must keep the changes of exchange rate less than 27.7059, due to exchange rate can affect current account adjustment, so can anticipate if there is current account deficit in Indonesia economy.  Keywords : Exchange Rate Flexibility, Current Account Adjustment, Exchange Rate Regime, Classification, Threshold VAR